Upaya Meningkatkan Mobilitas Fisik Dengan Latihan Mobilisasi Dini Pada Pasien Post Sectio Caesarea Di RSUD Sleman D.I Yogyakarta - Nurul Isnaini F; Anita Sari; Endriyatno Sulastomo (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Background: Sectio Caesarea is a method of giving birth to a fetus by making an incision in the uterine wall through the front wall of the abdomen (Amru Sofian, 2013). Giving birth by cesarean can drain more energy on the body and the recovery process takes longer. To speed up the recovery process, early mobilization exercises are needed. However, there are several factors that prevent mothers from doing early mobilization For this reason, it is important that efforts to increase early mobilization are carried out in order to speed up the healing process. Objective: To describe the description of nursing care in post sectio caesarea patients in practicing early mobilization. Research Methods: This study uses a literature review method in a journal that discusses early mobilization in post sectio caesarea mothers. Research Results: The results of the research from the literature review that the authors obtained through 10 journals, namely the mobilization efforts of post-SC postpartum mothers in carrying out early mobilization are influenced by pain in the surgical wound, knowledge/experience, motivation and beliefs. These results are relevant to the case managed by the author, namely Mrs. K was reluctant to do early mobilization because of pain and fear. Conclusion: From the results of the literature study above, it can be concluded that early mobilization of post sectio caesarea mothers can be improved by implementing pain management nursing, motivation, education and support from families and health workers